Fixed Point Theorems for Various Classes of Cyclic Mappings - Hassen Aydi; Erdal Karapınar; Bessem Samet (Journal of Applied Mathematics)
We introduce new classes of cyclic mappings and we study the existence and uniqueness of fixed points for such mappings. The presented theorems generalize and improve several existing results in the literature.